2015
DOI: 10.1021/acs.jpca.5b07459
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Investigation of Parylene D Thin Films: Relaxation and Conduction Mechanisms

Abstract: Parylene is a generic name indicating a family of polymers with the basic chemical structure of poly-p-xylylene. Parylene N and Parylene C are the most popular for applications. Curiously, Parylene D (poly( dichloro-p-xylylene), (C8H6Cl2)) was forgotten for applications. This report is the consequence of a later availability of a commercial dimer of Parylene D and also to the recent advent of fluorinated Parylenes allowing extending applications at higher temperatures. In our work, from a dielectric analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For frequencies higher than f h , the relaxation of the polarization cloud is in-phase with the outer electrical field resulting in short-time ion dynamics characterized by back and forth motion over limited ranges . This total conductivity behavior due to hopping ion transport obeys the well-known universal dielectric response (UDR), namely, Jonscher’s relation. Oil Sands 1, which has the least amount of water and clays, clearly obeys Jonscher’s relation: where f h indicates hopping frequency corresponding to the conduction relaxation time, σ dc is the limiting value of σ T ′ when ω → 0, and the s parameter depends on temperature, morphology, and composition and should be 0 ≤ s ≤ 1. Following this universal law indicates that conduction in Oil Sands 1 could be a case of ion motion by activated hopping between charge compensating sites. , It can be observed that the hopping frequency f h separating the short-range conduction process (ac conduction) from long-range conduction process (dc conduction) shifts toward the higher frequency regime as we go from Oil Sands 2 to 4 indicating that increasing water and clay content causes dc conduction to dominate.…”
Section: Resultsmentioning
confidence: 92%
“…For frequencies higher than f h , the relaxation of the polarization cloud is in-phase with the outer electrical field resulting in short-time ion dynamics characterized by back and forth motion over limited ranges . This total conductivity behavior due to hopping ion transport obeys the well-known universal dielectric response (UDR), namely, Jonscher’s relation. Oil Sands 1, which has the least amount of water and clays, clearly obeys Jonscher’s relation: where f h indicates hopping frequency corresponding to the conduction relaxation time, σ dc is the limiting value of σ T ′ when ω → 0, and the s parameter depends on temperature, morphology, and composition and should be 0 ≤ s ≤ 1. Following this universal law indicates that conduction in Oil Sands 1 could be a case of ion motion by activated hopping between charge compensating sites. , It can be observed that the hopping frequency f h separating the short-range conduction process (ac conduction) from long-range conduction process (dc conduction) shifts toward the higher frequency regime as we go from Oil Sands 2 to 4 indicating that increasing water and clay content causes dc conduction to dominate.…”
Section: Resultsmentioning
confidence: 92%
“…The dimer vaporizer was set at 175 °C, the pyrolysis furnace at 700 °C, and the deposition chamber was kept at room temperature (≈25 °C). Detailed information on the deposition process of Parylene D and its polymerization is available in other articles . Parylene D was chosen as a passivating coating because of its excellent chemical stability, high dielectric strength, and superior barrier properties, as well as its favorable failure strain (10%)…”
Section: Methodsmentioning
confidence: 99%
“…Due to this feature, lead chalcogenides become a better candidate for a tremendous number of applications. [20][21][22][23][24][25][26][27][28][29] Examples of their potential applications are solar cells , telecommunications, 23 eld effect transistors (FET), 24 and sensitive membrane materials for developing conventional chemical sensors selective to metal ions in liquid media, as well as biological imaging. 25,26 The aim of the present investigation was to study the effect of Se atom replacement by Pb atoms on the electrical properties of a multi-component system.…”
Section: Introductionmentioning
confidence: 99%